Synthesis of 4-Substituted-1,2-Dihydroquinolines by Means of Gold-Catalyzed Intramolecular Hydroarylation Reaction of N-Ethoxycarbonyl-N-Propargylanilines - Arcadi, Antonio (Molecules, 2021)
An alternative Au(I)-catalyzed synthetic route to functionalized 1,2-dihydroquinolines is reported. This novel approach is based on the use of N-ethoxycarbonyl protected-N-propargylanilines as building blocks that rapidly undergo the IMHA reaction affording the 6-endo cyclization product in good to high yields. In the presence of N-ethoxycarbonyl-N-propargyl-meta-substituted anilines, the regiodivergent cyclization at the ortho-/para-position is achieved by the means of catalyst fine tuning.